1994
DOI: 10.1016/s0022-5223(94)70370-1
|View full text |Cite
|
Sign up to set email alerts
|

Extension of tissue survival time in multiorgan block preparation with a delta opioid DADLE ([D-Ala2,D-Leu5]-enkephalin)

Abstract: , wei reported our results with a newly developed, autoperfused, multiorgan block preparation for long-term organ

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
24
0
4

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(28 citation statements)
references
References 6 publications
0
24
0
4
Order By: Relevance
“…Studies implicate an opioid‐like agent in this powerful adaptation, the levels of which increase in hibernation to induce beneficial effects in a DOR‐dependent manner, including myocardial tolerance to injurious insult (Bruce et al ., ; Bolling et al ., ; Kevelaitis et al ., ). Treatment with exogenous DOR‐selective opioids can also induce hibernation states in multiple species, and enhance organ stress resistance (Oeltgen et al ., ; Chien et al ., ). As with cardiac protection via opioid receptor agonists and opioid receptor‐dependent ischaemic preconditioning, the beneficial effects of hibernation involve activation of ATP‐sensitive K + (K ATP ) channels (Kevelaitis et al ., ).…”
Section: The Opioid Receptor System Orchestrates Cellular To Organismmentioning
confidence: 97%
“…Studies implicate an opioid‐like agent in this powerful adaptation, the levels of which increase in hibernation to induce beneficial effects in a DOR‐dependent manner, including myocardial tolerance to injurious insult (Bruce et al ., ; Bolling et al ., ; Kevelaitis et al ., ). Treatment with exogenous DOR‐selective opioids can also induce hibernation states in multiple species, and enhance organ stress resistance (Oeltgen et al ., ; Chien et al ., ). As with cardiac protection via opioid receptor agonists and opioid receptor‐dependent ischaemic preconditioning, the beneficial effects of hibernation involve activation of ATP‐sensitive K + (K ATP ) channels (Kevelaitis et al ., ).…”
Section: The Opioid Receptor System Orchestrates Cellular To Organismmentioning
confidence: 97%
“…The cardioprotection conferred by TAN-67 was subsequently reversed with the use of the selective ␦ 1 antagonist 7-benzylidenenaltrexone (BNTX). Chien et al (5) also reported that ␦ 1 -agonists helped to preserve the viability of multiorgan preparations. Because the activation of cholinergic receptors has also been implicated in cardioprotection (34), a potential link between opioids and vagal function might be physiologically important.…”
mentioning
confidence: 99%
“…S elective d receptor agonists have been shown to confer ischemic preconditioning (IPC) to myocardium, 1-6 brain, 7-9 multiorgan blocks, 10 and myocardial cell culture. 11 d receptor agonists specific for d 1 and d 2 receptor subtypes have also been shown to provide delayed (24-48 hours) or pharmacologic ischemic precon-ditioning (PPC) to ischemic myocardium.…”
mentioning
confidence: 99%
“…[12][13][14][15] The IPC and PPC are believed to operate through a mechanism(s) requiring activation of G i/o proteins, 15,16 translocation of protein kinase C d isoform 17 and subsequent activation of mitochondrial and sarcolemmal K ATP channel opening, 15,18,19 and lessening of myocardial oxygen requirements. [3][4][5][6][7][8][9][10] Polyubiquitin expression has also been implicated in the response to ischemic stress both in heart and brain. 20,21 We have recently demonstrated that IPC with the highly specific d 2 receptor agonist Deltorphin-D variant (Delt-D var ), but not the nonspecific d receptor agonist D-Ala 2 -Leu 5 -Enkephalin (DADLE), resulted in significantly reduced total polyubiquitin transcript expression in rat myocardium, thereby indicating d 2 opioid IPC modulation of the ubiquitin stress pathway.…”
mentioning
confidence: 99%